2011
DOI: 10.2991/ijcis.2011.4.3.13
|View full text |Cite
|
Sign up to set email alerts
|

Driver Intention Recognition Method Using Continuous Hidden Markov Model

Abstract: In order to make Intelligent Transportation System (ITS) work effectively, a driver intention recognition method is proposed. In this research, three different recognition models were developed based on Continuous Hidden Markov Model (CHMM), and could distinguish left and right lane change intention from normal lane keeping intention. Subjects performed lane change maneuvers and lane keeping maneuvers with driving simulator which simulated highway scenes, parameters that highly correlated with lane change beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…One of the limitations to be emphasised is the sequential nature of the decisions of the original model, which causes a decision to invalidate multiple branches in the lane change decision tree, causing discretionary lane changes hardly to be selected. This limitation has been addressed with traditional techniques, generally based on approximate reasoning, such as probabilistic trees [ 15 ] or Hidden Markov Models [ 16 ]. However, the problem remains in the fact that, to improve the predictive capacity of these models it is necessary to extend the number of input variables, with the consequent increase in the relationships between them and, therefore, the complexity of the models.…”
Section: Literature Reviewmentioning
confidence: 99%
“…One of the limitations to be emphasised is the sequential nature of the decisions of the original model, which causes a decision to invalidate multiple branches in the lane change decision tree, causing discretionary lane changes hardly to be selected. This limitation has been addressed with traditional techniques, generally based on approximate reasoning, such as probabilistic trees [ 15 ] or Hidden Markov Models [ 16 ]. However, the problem remains in the fact that, to improve the predictive capacity of these models it is necessary to extend the number of input variables, with the consequent increase in the relationships between them and, therefore, the complexity of the models.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Weidl et al 15 optimized a Bayesian recognition network to distinguish a manoeuvre in order to reduce the average computation time. Three different identification models based on a continuous HMM were developed to identify the left-lane-change intentions and right-lanechange intentions from the normal lane-keeping intention by Hou et al 16 Berndt and Dietmayer 17 also investigated a method based on an HMM to infer a driver's intention to leave the lane-following state or the carfollowing state and to start a specific manoeuvre from the easily accessible vehicle onboard sensors.…”
Section: Introductionmentioning
confidence: 99%
“…Dou et al [24] suggested that combining an SVM and a neural network by using weight allocations could improve the recognition rate for lane changes; vehicle data were extracted, including horizontal and vertical coordinates, speed, and type, from the next-generation simulation (NGSIM) database. Haijing et al [25] developed an identification model for lane change intention that integrated a hybrid Gaussian HMM with a SVM and used the standard deviation of the horizontal angle of the driver's head, the number of times the driver gazed at the rear-view mirror, the average scanning range, and the steering wheel angle entropy as input parameters. Semantic segmentation and target detection based on deep learning techniques have been used to detect the motion state of the target using data derived from stereo cameras and LIDAR [26]- [29].…”
Section: Introductionmentioning
confidence: 99%